Do aerobic characteristics explain isometric exercise-induced neuromuscular fatigue and recovery in upper and lower limbs?. Issue 4 (16th February 2019) - Vernillo, Gianluca; Temesi, John; Martin, Matthieu; Millet, Guillaume Y.
ABSTRACT: This study investigated the relationships between aerobic characteristics and (i) neuromuscular fatigue induced by 2-min sustained isometric maximal voluntary contractions (MVC) and (ii) subsequent recovery, in the upper and lower limbs. In a pseudo-randomized order, eleven healthy males completed four sessions on different days: maximal incremental cycling test (100 W + 40 W every 2 min); maximal arm-cranking test (50 W + 20 W every 2 min); and 2-min sustained isometric MVCs of the knee extensors (KE) and elbow flexors (EF). Neuromuscular assessment was performed with transcranial magnetic and peripheral nerve stimulation to evaluate central and peripheral neuromuscular factors of fatigue and the subsequent recovery. Peak oxygen uptake, gas exchange threshold and the corresponding power outputs were correlated with recovery of voluntary force after the 2-min KE MVC. Regression analysis showed that power output at the gas exchange threshold alone explained 72% of the variability in ∆recovery of KE voluntary force. No relationships with fatigue or recovery in EF were observed. These results suggest that participants with greater aerobic capacities experience the same amount of fatigue and faster recovery of voluntary force in KE but not EF. The potential reasons behind the relationship in KE but not EF are discussed.